Year to year variation in sea buckthorn juice volatiles using headspace solid phase microextraction. (5th November 2015) - Leung, Gee‐Sian; Marriott, Ray
Abstract: This study highlights the use of optimised headspace solid phase microextraction (HS‐SPME) to capture over 70 volatile compounds from three different varieties of sea buckthorn juice harvested from 2011 to 2013. The main components were identified as ethyl and 3‐methyl butyl esters which were quantified using deuterium labelled standards and synthesised as part of this work. Berries harvested over the three years showed variation in the concentration of the principle components that may be associated with weather variation. Previously unreported volatile compounds that may contribute to the unique aroma of sea buckthorn juice were also identified. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This study highlights the use of optimised headspace solid phase microextraction (HS‐SPME) method to capture over 70 volatile compounds from three different varieties of in sea buckthorn juice harvested from 2011‐2013. The main components were identified as ethyl and 3‐methyl butyl esters which were quantified using deuterium labelled standards.